2021
DOI: 10.1111/bjh.17499
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analysis of ICARIA‐MM study in relapsed/refractory multiple myeloma patients with high‐risk cytogenetics

Abstract: Summary Treatment benefit in multiple myeloma (MM) patients with high‐risk cytogenetics remains suboptimal. The phase 3 ICARIA‐MM trial (NCT02990338) showed that isatuximab plus pomalidomide–dexamethasone prolongs median progression‐free survival (mPFS) in patients with relapsed/refractory MM (RRMM). This subgroup analysis of ICARIA‐MM compared the benefit of isatuximab in high‐risk [defined by the presence of del(17p), t(4;14) or t(14;16)] versus standard‐risk patients. The efficacy of isatuximab in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Two things interesting were that, the ORR of CT053 to treat the RRMM patients relapsed after three or more LOT with the extramedullary disease (EMD) being 91.7%, the CR rate being 58.3%, and the median PFS being 9.3 months, better than the results of those past treatment strategies such as combination therapy with permadomide and dexamethasone (ORR: 30%; CR rate: 15.3%) ( 69 ) and carfilzomib-based combination therapy (ORR: 27%, CR rate: 0%, median PFS: 5 months) ( 70 ). For the patients with high-risk cytogenetic abnormalities [del(17p), t(4;14), t(14;16)/1q21], the ORR and CR rate of CT053 were 84.2% and 73.3%, respectively, with the 15.6 months median PFS, better than the results of ishatuximab, permadomide, and dexamethasone combination (ORR: 50%, CR rate: 0%, median PFS: 7.5 m) ( 71 ), carfilzomib monotherapy (ORR: 25.8%, CR rate: 0%, median PFS: 3.5 m) ( 72 ), and even the infusion of bb2121 (ORR: 73%, CR rate: 33%, median PFS: 8.2 m) ( 60 ). Secondly, the relationship between the dosage and curative effect of C-CAR088 has been studied ( 52 ).…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…Two things interesting were that, the ORR of CT053 to treat the RRMM patients relapsed after three or more LOT with the extramedullary disease (EMD) being 91.7%, the CR rate being 58.3%, and the median PFS being 9.3 months, better than the results of those past treatment strategies such as combination therapy with permadomide and dexamethasone (ORR: 30%; CR rate: 15.3%) ( 69 ) and carfilzomib-based combination therapy (ORR: 27%, CR rate: 0%, median PFS: 5 months) ( 70 ). For the patients with high-risk cytogenetic abnormalities [del(17p), t(4;14), t(14;16)/1q21], the ORR and CR rate of CT053 were 84.2% and 73.3%, respectively, with the 15.6 months median PFS, better than the results of ishatuximab, permadomide, and dexamethasone combination (ORR: 50%, CR rate: 0%, median PFS: 7.5 m) ( 71 ), carfilzomib monotherapy (ORR: 25.8%, CR rate: 0%, median PFS: 3.5 m) ( 72 ), and even the infusion of bb2121 (ORR: 73%, CR rate: 33%, median PFS: 8.2 m) ( 60 ). Secondly, the relationship between the dosage and curative effect of C-CAR088 has been studied ( 52 ).…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…40 Cytogenetics was not a significant covariate in the joint model, on either serum M-protein dynamics or PFS, in agreement with ICARIA-MM subgroup analyses, which showed that Isa-Pd provided consistent benefit versus Pd in RRMM patients, regardless of cytogenetic risk. 41 The drug-disease modelling platform established based on ICARIA-MM data was further applied to predict the impact of using a hypothetical monthly dosing regimen after 6 months of Isa QW-Q2W in RRMM patients. In patients still on treatment, simulations of a hypothetical switch to monthly dosing after 6 months predicted progression to occur 2.3 weeks earlier compared with the original Isa-Pd arm, with 42.3% of patients having their serum M-protein regrow faster.…”
Section: Simulation Of Monthly Dosing Regimenmentioning
confidence: 99%
“…The addition of isatuximab to pomalidomide–dexamethasone significantly improved PFS in patients with RRMM (Table 1 ); the risk of disease progression or all-cause death was reduced by 40% [hazard ratio (HR) 0.596, 95% CI 0.436–0.814; p = 0.001] at the time of the primary analysis [ 28 ]. A PFS benefit was seen with the addition of isatuximab to pomalidomide–dexamethasone in all prespecified subgroups, including patients aged ≥ 75 years, those at ISS stage III, those with RI, those with high-risk cytogenetics, those with 2–3 or > 3 previous lines of therapy, those refractory to lenalidomide, those refractory to a PI, and those double-refractory to lenalidomide and a PI [ 28 , 41 , 42 ]. Moreover, in retrospective analyses, PFS benefits were seen with the addition of isatuximab to pomalidomide–dexamethasone in the following subgroups of patients: those with isolated gain of chromosome arm 1q21 genomic abnormality (1q21 gain; ≥ 3 copies of 1q21); those with 1q21 gain, regardless of the presence of other high-risk cytogenetic abnormalities; those with isolated amplification of chromosome arm 1q21 genomic abnormality (1q21 amplification; ≥ 4 copies of 1q21); and those with 1q21 amplification (≥ 4 copies of 1q21), regardless of the presence of other high-risk cytogenetic abnormalities [ 42 ].…”
Section: Therapeutic Efficacy Of Isatuximabmentioning
confidence: 99%
“…Adding isatuximab to pomalidomide–dexamethasone significantly improved ORR (Table 1 ). Consistent with the ORR benefit seen in the overall population [odds ratio (OR) 2.795, 95% CI 1.75–4.56; p < 0.0001], ORRs were numerically higher with isatuximab–pomalidomide–dexamethasone than with pomalidomide–dexamethasone in all prespecified subgroups, including patients aged ≥ 75 years, those with RI, those with high-risk cytogenetics, those with 2–3 or > 3 previous lines of therapy, those refractory to lenalidomide, and those double-refractory to lenalidomide and a PI [ 28 , 41 , 42 ]. ORRs were, respectively, 53.6% and 27.6% in isatuximab-pomalidomide–dexamethasone and pomalidomide–dexamethasone recipients with isolated 1q21 gain (one-sided p = 0.0116) [ 42 ] and 52.1% and 34.2% in isatuximab–pomalidomide–dexamethasone and pomalidomide–dexamethasone recipients classified as frail ( p < 0.05) [ 39 ].…”
Section: Therapeutic Efficacy Of Isatuximabmentioning
confidence: 99%